Safety evaluation of the food enzyme alternansucrase from the genetically modified Escherichia coli strain EBASSC - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal, 2025)
Abstract The food enzyme alternansucrase (sucrose:1,6(1,3)‐α‐d‐glucan 6(3)‐α‐d‐glucosyltransferase; EC 2.4.1.140) is produced with the genetically modified Escherichia coli strain EBASSC by Advanced Enzyme Technologies Ltd. The production strain of the food enzyme contains a known antimicrobial resistance gene. However, based on the absence of viable cells and DNA from the production organism in the food enzyme, this is not considered to be a risk. The food enzyme is intended to be used in the processing of sugars for the production of maltose alternan gluco‐oligosaccharides. Two sets of dietary exposure estimates were made, using the default or more specific input factors. The refined dietary exposure was estimated to be up to 0.586 mg total organic solids (TOS)/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 500 mg TOS/kg bw per day, the mid‐dose tested, which when compared with the refined exposure estimate, results in a margin of exposure of at least 853. A search for the homology of the amino acid sequence of the alternansucrase to known allergens was made and no match was found. The Panel considered that a risk of allergic reactions upon dietary exposure to the food enzyme cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.